2012
DOI: 10.1073/pnas.1206411109
|View full text |Cite
|
Sign up to set email alerts
|

Link between intraphagosomal biotin and rapid phagosomal escape in Francisella

Abstract: Cytosolic bacterial pathogens require extensive metabolic adaptations within the host to replicate intracellularly and cause disease. In phagocytic cells such as macrophages, these pathogens must respond rapidly to nutrient limitation within the harsh environment of the phagosome. Many cytosolic pathogens escape the phagosome quickly (15-60 min) and thereby subvert this host defense, reaching the cytosol where they can replicate. Although a great deal of research has focused on strategies used by bacteria to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 35 publications
3
60
0
Order By: Relevance
“…In contrast to the results in Histoplasma, both Mycobacterium tuberculosis and Candida biotin auxotrophs are impaired in intracellular replication (11,67,68,72). Furthermore, initial escape from the phagosome for Francisella also requires biotin biosynthesis (73). On the other hand, Salmonella biotin and pantothenate auxotrophs are not attenuated (74).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the results in Histoplasma, both Mycobacterium tuberculosis and Candida biotin auxotrophs are impaired in intracellular replication (11,67,68,72). Furthermore, initial escape from the phagosome for Francisella also requires biotin biosynthesis (73). On the other hand, Salmonella biotin and pantothenate auxotrophs are not attenuated (74).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings imply, in addition, that the metabolic adaptation of intracytosolic microbes is a necessary, but alone not sufficient, factor for their replication and that an intricate host-bacterium interaction is required for the intracytosolic replication. In fact, using the microinjection technique, we previously demonstrated its utility to directly elucidate metabolic requirements for cytosolic replication, since it was demonstrated that a biotin biosynthesis mutant of Francisella novicida was incapable of intracytosolic growth unless biotin was added to the culture medium (19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was hypothesized that bacteria which successfully replicate in the cytosol harbor a metabolic machinery that is adapted to this niche in order to utilize available nutrients (14). However, there is accumulating evidence that the metabolic requirements may be similar for bacteria residing within the eukaryotic cytosol and bacteria residing extracellularly (15)(16)(17)(18)(19), thus indicating that modulation of the cytosolic composition, e.g., by deprivation of the availability of metabolites, may be an important factor to control replication of intracellular bacteria. To add further complexity, there is recent evidence that manipulation of autophagy is used as a means by pathogens to acquire energy and nutrients.…”
mentioning
confidence: 99%
“…Several genetic screens for replication-defective mutants have implicated biosynthetic pathways as contributing factors to the pathogenesis of Francisella species (16). Interruption in genes involved in purine, aromatic amino acid, and biotin biosynthesis results in attenuation of F. tularensis within a mouse model of tularemia (17)(18)(19)(20). Collectively, these studies highlight the contribution of de novo biosynthetic pathways to the ability of F. tularensis to survive within the host environment.…”
mentioning
confidence: 95%